EVALUATION OF EFFICACY OF AROHANAKRAMA SNEHAPANA AND VIRECHANA IN THE MANAGEMENT OF ADHOGAAMLAPITTA (International Journal of Ayurveda and Pharma Research, 2018)
Amlapitta is one of the leading problems of new era due to irregular and improper diet, dietetics and stressful life style. It is a very common disorder of Annavahasrotasa caused by Vidagdha Pitta with features like, Abipaka (indigestion), Klama (fatigue), Utklesha (nausea), Tikta-Amlodgara (sour or bitter eructation), Gourava (heaviness), Hritkanthadaha (heart burn), Aruchi (anorexia) etc., Amlapitta include acid peptic disorders (APD)- gastroesophageal reflux disease (GERD), Peptic ulcer diseases (PUD), dyspepsia and functional disorder of GI tract, In the present study, aimed to compare the efficacy of Jeerakadya Ghrita Arohanakrama Snehapana (increasing order) followed by Virechana with Trivrit Churnaadi yoga and Patolashunti Ghrita Arohanakrama Snehapana followed by Virechana with Trivritchurnadi yoga in the management of Adhoga Amlapitta. Material and methods: A minimum of 30 patients suffering from Adhoga Amlapitta were selected in 2 groups, 15 patients in each group. Group A- 15 patients were given Jeerakadya Ghrita Arohanakramasnehapana and Virechana. Group B-15 patients were given Patolashunti Ghrita Arohanakramasnehapana and Virechana. Follow up for 14 days (Patients will be assessed clinically on day 0, 7th day & 14th day). Total study duration is 35days. Virechana is highly significant on all the parameters, except Bhrama at both the phases. Statistical analysis of Group A and Group B are showing same result, but there will be reduction percentage in sign and symptoms like Agnimagda, Trishna, Hrillasa, Bhrama, Vividhavarnayoukta Malapravritti Group A is given better result.